2022
DOI: 10.1111/mec.16728
|View full text |Cite
|
Sign up to set email alerts
|

Diversification linked to larval host plant in the butterflyEumedonia eumedon

Abstract: Ecological speciation occurs when reproductive isolation evolves between populations as a result of ecologically based divergent selection (Rundle & Nosil, 2005). The environmental elements that cause divergent selection are diverse and comprise a wide range of abiotic and biotic factors, including interactions with other species (Nosil, 2012). In the case of phytophagous insects, divergent selection can occur as a result of a specialization of the insect to its host plant (Tilmon, 2008), which may lead to a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 132 publications
2
4
0
Order By: Relevance
“…Despite the clear patterns of genetic structure present in this species, F ST values between populations of Hayden's ringlets were low to moderate. The scale of differentiation we observed is consistent with fine‐ to moderate‐scale genetic population structure ( F ST between 0.01 and 0.2) seen in other non‐migratory butterfly species (Hinojosa et al., 2023; Pertoldi et al., 2021; Talla et al., 2019, 2023), and on average greater than in migratory species like monarchs (FST=0.0001) (Talla et al., 2020). While the F ST values we observed may be considered low in other groups of organisms, in many cases F ST values between nominal species of butterflies are not considerably greater than what we found within populations of the Hayden's ringlet (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the clear patterns of genetic structure present in this species, F ST values between populations of Hayden's ringlets were low to moderate. The scale of differentiation we observed is consistent with fine‐ to moderate‐scale genetic population structure ( F ST between 0.01 and 0.2) seen in other non‐migratory butterfly species (Hinojosa et al., 2023; Pertoldi et al., 2021; Talla et al., 2019, 2023), and on average greater than in migratory species like monarchs (FST=0.0001) (Talla et al., 2020). While the F ST values we observed may be considered low in other groups of organisms, in many cases F ST values between nominal species of butterflies are not considerably greater than what we found within populations of the Hayden's ringlet (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The combination of this approach with ddRADseq data from insects has been proven to extract reliable information on the infection of host individual samples by bacterial endosymbionts (Hinojosa et al . 2022, 2023). Briefly, reads matching to Wolbachia genomes were extracted and subjected to a comprehensive quality filtering pipeline as detailed in Supplementary Methods S5.…”
Section: Methodsmentioning
confidence: 99%
“…This novel approach has been proven to provide reliable and sensitive inferences on the presence and abundance of bacterial endosymbionts in ddRADseq data from insect samples (Hinojosa et al . 2019, 2020, 2022, 2023). CENTRIFUGE was run with default settings and using the most updated Archaea and Bacteria index provided by CENTRIFUGE developers (https://genome-idx.s3.amazonaws.com/centrifuge/p_compressed_2018_4_15.tar.gz), which is composed of 3,333 complete reference genomes.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…For example, Hinojosa et al. ( 2023 ) suggested that the use of different plants has led to reproductive isolation for Eumedonia eumedon (Esper, 1780). Alternatively, plant availability or plant quality may be significant.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of different plant species in different regions or habitats could indicate cryptic speciation. For example, Hinojosa et al (2023) suggested that the use of different plants has led to reproductive isolation for Eumedonia eumedon (Esper, 1780).…”
mentioning
confidence: 99%